Malate-aspartate shuttle inhibitor aminooxyacetic acid leads to decreased intracellular ATP levels and altered cell cycle of C6 glioma cells by inhibiting glycolysis. Issue 1 (1st August 2016) - Wang, Caixia; Chen, Heyu; Zhang, Mingchao; Zhang, Jie; Wei, Xunbin; Ying, Weihai
Highlights: AOAA treatment can selectively decrease C6 glioma cell survival. AOAA decreased the ATP levels without affecting the △Ψm of C6 glioma cells. AOAA treatment led to decreased glycolytic rate of C6 glioma cells. Pyruvate treatment prevented the toxic effects of AOAA on C6 glioma cells. Abstract: NADH shuttles, including malate-aspartate shuttle (MAS) and glycerol-3-phosphate shuttle, can shuttle the reducing equivalents of cytosolic NADH into mitochondria. It is widely accepted that the major function of NADH shuttles is to increase mitochondrial energy production. Our study tested the hypothesis that the novel major function of NADH shuttles in cancer cells is to maintain glycolysis by decreasing cytosolic NADH/NAD + ratios. We found that AOAA, a widely used MAS inhibitor, led to decreased intracellular ATP levels, altered cell cycle and increased apoptosis and necrosis of C6 glioma cells, without affecting the survival of primary astrocyte cultures. AOAA also decreased the glycolytic rate and the levels of extracellular lactate and pyruvate, without affecting the mitochondrial membrane potential of C6 cells. Moreover, the toxic effects of AOAA were completely prevented by pyruvate treatment. Collectively, our study has suggested that AOAA may be used to selectively decrease glioma cell survival, and the major function of MAS in cancer cells may be profoundly different from its major function in normal cells: The major function of MAS in cancer cells is to maintain glycolysis, instead of increasing mitochondrial energy metabolism.